2018
DOI: 10.3390/nu10050593
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Highly Polymeric A-Type Proanthocyanidins from Seed Shells of Japanese Horse Chestnut (Aesculus turbinata BLUME) against Light-Induced Oxidative Damage in Rat Retina

Abstract: Retinal tissue is exposed to oxidative stress caused by visible light. Light-damaged rat used in age-related macular degeneration (AMD) studies clarified that antioxidants decrease retinal light damage. Albino rats were exposed to 5000 Lux light for 12 h with oral administration of the polyphenolic compounds fraction (PF) from the seed shells of Japanese horse chestnut (30 mg/kg, 100 mg/kg, and 300 mg/kg body weight: BW). To evaluate the protective effects against light damage, electroretinograms (ERGs), the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Similar observations have been reported for other substances of natural origin. Indeed, in the last few years a variety of nutraceuticals have been found to exert important antioxidant effects resulting in amelioration of ERG responses in different retinal disease or retinal injury models [32,33,34,35,36,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations have been reported for other substances of natural origin. Indeed, in the last few years a variety of nutraceuticals have been found to exert important antioxidant effects resulting in amelioration of ERG responses in different retinal disease or retinal injury models [32,33,34,35,36,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Seven days after the light exposure, flash ERGs were recorded (LS-W, Mayo Corporation, Aichi, Japan) according to previous reports [ 8 , 9 ]. Twenty minutes before the recording, the animals were anesthetized and the pupils dilated using the same methods as used for the light exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, with the widespread use of tablets and smartphones, it has been suggested that the blue light from these electronic devices using light-emitting diodes (LEDs) may cause blue-light hazard [ 7 ]. In addition, as it has become clear that oxidative stress is involved in the pathogenesis of age-related macular degeneration (AMD), antioxidants, such as polyphenols, that are effective in inhibiting the onset or progression of AMD have been actively pursued [ 8 , 9 ]. In these studies, animal models of light-induced retinal damage are often used, especially rats and mice, which are widely used because they are easy to maintain and treat.…”
Section: Introductionmentioning
confidence: 99%
“…The main herbal medicines recommended to treat ARMD include xanthophylls lutein, zeaxanthin, and ginkgo [42,48,51,52]. The literature also describes the photo-protective effect of berries [bilberry (Vaccinium myrtillus L.), cranberry (Vaccinium oxycoccos L.), blackcurrant (Ribes nigrum L.), wolfberry (Lycium barbarum L.), grapes (Vitis vinifera L.)], stigmas [such as saffron (Crocus sativus L.)], and roots and rhizomes [such as turmeric (Curcuma longa L.) and Dan Shen (Salvia miltiorrhiza Bunge) [36,48,50,[53][54][55][56][57][58][59] on age-related ocular diseases. Ginkgo has become an increasingly well-known medicinal plant worldwide, and is used to treat peripheral vascular disease and cerebral insufficiency [16,[22][23][24].…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%